BS EN 2939. Aerospace series. Screws, 100° countersunk head, offset cruciform recess, threaded to head, in heat resisting steel FE-PA92HT (A286). Classification. 900 MPa (at ambient temperature)/650 °C. (27th March 2023) - British Standards Institution,
No abstract available